Risk of Severe Acute Respiratory Syndrome Coronavirus 2 Transmission Through Solid Organ Transplantation and Outcomes of Coronavirus Disease 2019 Among Recent Transplant Recipients. (2nd May 2022) - Free, Rebecca J; Annambhotla, Pallavi; La Hoz, Ricardo M; Danziger-Isakov, Lara; Jones, Jefferson M; Wang, Lijuan; Sankthivel, Senthil; Levi, Marilyn E; Michaels, Marian G; Kuhnert, Wendi; Klassen, David; Basavaraju, Sridhar V; et al.
Abstract: Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is transmissible through lung transplantation, and outcomes among infected organ recipients may be severe. Transmission risk to extrapulmonary organ recipients and recent (within 30 days of transplantation) SARS-CoV-2–infected recipient outcomes are unclear. Methods: During March 2020–March 2021, potential SARS-CoV-2 transmissions through solid organ transplantation were investigated. Assessments included SARS-CoV-2 testing, medical record review, determination of likely transmission route, and recent recipient outcomes. Results: During March 2020–March 2021, approximately 42 740 organs were transplanted in the United States. Forty donors, who donated 140 organs to 125 recipients, were investigated. Nine (23%) donors and 25 (20%) recipients were SARS-CoV-2 positive by nucleic acid amplification test (NAAT). Most (22/25 [88%]) SARS-CoV-2–infected recipients had healthcare or community exposures. Nine SARS-CoV-2–infected donors donated 21 organs to 19 recipients. Of these, 3 lung recipients acquired SARS-CoV-2 infections from donors with negative SARS-CoV-2 testing of pretransplant upper respiratory tract specimens but from whom posttransplant lower respiratory tract (LRT) specimens were SARS-CoV-2 positive. Sixteen recipients of extrapulmonary organs from SARS-CoV-2–infected donors had no evidence of posttransplant COVID-19. All-cause mortality within 45 days after transplantation was 6-fold higher among SARS-CoV-2–infected recipients (9/25 [36%]) than those without (6/100 [6%]). Conclusions: Transplant-transmission of SARS-CoV-2 is uncommon. Pretransplant NAAT of lung donor LRT specimens may prevent transmission of SARS-CoV-2 through transplantation. Extrapulmonary organs from SARS-CoV-2–infected donors may be safely usable, although further study is needed. Reducing recent recipient exposures to SARS-CoV-2 should remain a focus of prevention.